Antioxidant properties of different strains of Kappaphycus alvarezii (Rhodophyta) farmed on the Brazilian coast. Issue 3 (3rd May 2020) - Araújo, Patrícia G.; Nardelli, Allyson E.; Fujii, Mutue T.; Chow, Fungyi
ABSTRACT: Kappaphycus alvarezii: is one of the most farmed algae globally. It is used almost exclusively for the carrageenan industry, although there is increasing interest in its biotechnological application as a natural product with biological properties. This cultivated species produces different strains with distinct chemical and physiological properties. Despite this, K. alvarezii has been marketed as a single biomass. The aim of this study was to evaluate differences in antioxidant capacities among green, red, brown and G11 strains of K. alvarezii cultivated in southeastern Brazil, assessed by Folin–Ciocalteu reducing potential, DPPH, ABTS and FRAP assay methods. Methanolic and aqueous extracts yielded from 2.67% to 3.43% and 26.25% to 32.90%, respectively. Nevertheless, methanolic extracts showed higher total phenolic content (40.80 mg GAE 100 g −1 DW to 58.49 mg GAE 100 g −1 DW) than aqueous ones (7.77 mg GAE 100 g −1 DW to 12.51 mg GAE 100 g −1 DW), and a similar trend was found for DPPH (7.15% to 31.21%), for ABTS (60.29% to 100.39%), and for FRAP (27.24% to 95.95%). Antioxidant activity of aqueous extracts was lower than 17% for all spectrophotometric assays. The green strain had the highest index of antioxidant capacity, suggesting that this strain may be suitable as a natural source of antioxidants. This is the first report evaluating antioxidant potential of four strains of K. alvarezii, supporting the need for further research to identify and select for its value as a viable natural antioxidant source.